Aplicación de un modelo de ecuaciones estructurales para analizar los sistemas de gestión en la integración de la RSC y su influencia en la estrategia y el performance de las empresas tecnológicas - Juan Andrés Bernal Conesa; Carmen de Nieves Nieto; Antonio Juan Briones Pe\~nalver (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– The importance of management systems for the integration of CSR in the company strategy is a vital resource that has been little studied in technology companies. In this paper a structural equation model is proposed in order to explain the in uence of CSR and its integration into the management system of the company. This in uence is facilitated by the existence of previous standardized management systems, and how this integration affects the strategy of the company and if this is a reflection on the economic performance of the technology company. The study was conducted in companies located in Spanish Science and Technology Parks. On the one hand, model results shows that there is a positive, direct and statistically significant relationship between the integration of CSR and strategy; on the other hand, performance and integration has also this relationship. Likewise, the model shows also some indirect evidence relations between Management System before the implementation of CSR and performance.
Keywords: M14; 330; structure equation modeling; corporate social responsibility; technology companies; integration; performance